Asexual reproduction strategies in the moon jellyfish Aurelia (Cnidaria: Scyphozoa) - Wang, Fanghan; Schiariti, Agustin; Xu, Shengnan; Ma, Yuanqing; Sun, Tingting; Wang, Lei; Zhao, Jianmin; Dong, Zhijun (Frontiers in Ecology and Evolution, 2023)
The genus Aurelia is one of the major contributors to jellyfish blooms in coastal waters, possibly due to its adaptive reproduction strategies. Different Aurelia lineages have adapted their reproduction modes to varying environmental conditions in their respective habitats. To understand the successful adaptation strategies, three strains of A. coerulea and two strains of A. solida polyps from different geographical areas were exposed to a range of temperatures and two food regimes, and the effects on reproduction rates were assessed. Asexual reproduction was significantly affected by the changes in these factors. The highest reproduction rate under sufficient food conditions was observed in the USA strain and the lowest was observed in the Israel strain, regardless of temperature, indicating the differences in the blooming potential. Six asexual reproduction modes were observed, of which lateral budding, lateral budding by means of stolons, and reproduction from parts of stolons were the main modes used by all Aurelia strains, except A. solidaISR, for which reproduction by stolons was the main mode. The capability to switch reproductive strategies in response to environmental cues depending on the lineage predetermines the highly frequent blooming events of Aurelia.